The biology of exosomes and exosomal non-coding RNAs in cardiovascular diseases - Gan, Lu; Guo, Xiaofei; Dong, Shichao; Sun, Chuan (Frontiers in Pharmacology, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of death worldwide, both in developed and developing countries. Despite the implementation of various measures in clinical practice that have shown certain curative effects, poor prognosis and irreversible pathological cardiac remodeling continue to limit the therapeutic effect of CVDs. There are still many new mechanisms worth exploring for the regulation of CVDs. Previous studies have highlighted the potential applicability of exosomes in CVDs, and significant research has been conducted in this area. In this review, we summarize the physiological mechanisms of exosomes and the basic research achievements in regulating CVDs via exosomal non-coding RNAs. We also discuss the limitations and prospects of exosome application in CVD treatment.